A comparative analysis of primary antiretroviral therapy outcomes by service provider type in Blantyre District, Malawi - Chuka, Stuart, Rodney (2022)
The Antiretroviral Therapy (ART) Program for Malawi started in 2004 and the key providers in provision of ART services in Malawi include; the public sector, the private sector for-profit and non-profit and Christian Health Association of Malawi (CHAM). Since then, no known studies have been conducted to compare primary ART treatment outcomes by service provider type thus public, private and CHAM. In addition, information on variation of primary ART treatment outcomes by service provider type is not known and probably has not been published The Objective was to examine primary Antiretroviral Therapy outcomes in Blantyre District using ART data from 1st January 2017 to 31st December, 2018 in public, private and Christian Health Association of Malawi ART clinics This was a cross-sectional study and utilized both quantitative and qualitative methods. The quantitative method used facility level secondary data from the Malawi National ART Program in the Ministry of Health HIV AIDS Department. The qualitative method used in-depth interviews using an interview guide to key informants. Data was analysed using STATA statistical software package version 15.Analysis of Variance (ANOVA) was used to compare the variations of primary ART outcomes among in public, private and CHAM ART sites. To compare proportions, the researcher used Scheffe's-Test. The qualitative data was analyzed using thematic analysis to explain the relationship between the variables. Overall the findings indicate that Primary Antiretroviral Therapy Outcomes in Public, Private and CHAM ART Clinics are different. According to the results, there are more defaulters in the public ART clinics followed by private and lowest in the CHAM ART sites. This may be attributed lack of privacy and confidentiality, stigma and discrimination iv and long distance to the health facility which result in high cost expenses.Overall died on ART outcome is higher in private ART clinics compared to public and CHAM ART clinics and no significant differences between public and private ART clinics. The study has also clearly demonstrated that the private ART clinics have more transfer outs than public and CHAM due to change of location for work related issues of the clients. Retention in care (Alive on ART) is high in CHAM ART Clinics followed by public then lastly private. Generally, stop on ART is not a common outcome in all service provider types. Overall the findings indicate that Primary Antiretroviral Therapy Outcomes in Public, Private and CHAM ART Clinics are different. Some of the factors contributing to the primary Art outcomes include; lack of privacy and confidentiality, stigma and discrimination and long distance to the health facility which result in high cost expenses and change of location for work related issues of the clients. Generally, stop on ART is not a common outcome in all service provider types.